IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION OF A NARRATIVE TEXT THROUGH THINK PAIR SHARE TECHNIQUE - Rusli, Hajizan Taufid; Rufinus, Albert; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aimed at improving reading comprehension skill on narrative text through of the eighth grade students of SMP Islamiyah Pontianak in academic year 2012/2013 using Think Pair Share. Think Pair Share (TPS) is one of cooperative teaching strategies which can encourage students to actively engage in the class. In order to achieve the students‟ improvement, action research was conducted in three cycles. During the action it was found that the students mean score of students‟ reading comprehension in the first cycle was 58.83. the second cycle was 65.33. and the third cycle was 75.17. Those three mean scores had proved that Think Pair Share succeeded to improve the students‟ reading ability on narrative text. Keyword: Cooperative Learning, Think Pair Share Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan memahami teks narasi para siswa kelas VIII SMP Islamiyah Pontianak tahun ajaran 2012/2013 dengan menggunakan teknik Think Pair Share. Teknik Think Pair Share (TPS) adalah salah satu teknik pembelajaran kooperatif yang dapat mendorong siswa untuk lebih aktif belajar di kelas. Untuk mencapai perkembangan pemahaman membaca para siswa, Penelitian Tindak Kelas dilaksanakan selama tiga kali. Selama penelitian berlangsung, nilai rata – rata kelas pada siklus penelitian pertama adalah 58.83. nilai rata-rata kelas penelitian kedua adalah 65.33. nilai rata-rata kelas pada penelitian ketiga adalah 75.17. Ketiga nilai penelitian tersebut membuktikan bahwa Think Pair share telah berhasil meningkatkan kemampuan siswa dalam memahami sebuah teks narasi. Kata Kunci: Pembelajaran Kooperatif, Think Pair Share